2018
DOI: 10.1007/s11085-018-9876-z
|View full text |Cite
|
Sign up to set email alerts
|

Model About the Course of Corrosion Reactions of Austenitic Steels in H2S-, HCl- and CO2-Containing Atmospheres at 680 °C

Abstract: Material selection for thermal cracking processes of anthropogenic resources is challenging. H 2 S and HCl are formed, and corrosion occurs at high temperatures. Several steels were investigated in the past. In all cases, corrosion layers were characteristically structured. On top, large chromium sulfide crystals are located, followed by a Cr 2 O 3 layer, followed by a layer enriched in chlorine and nickel. In this paper, we propose a model on the course of the corrosion reactions. By considering the water-gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 24 publications
(39 reference statements)
2
33
0
Order By: Relevance
“…Thereby the findings of the EDX mappings and the XRD results can be explained. This mechanism has been identified in previous studies, and a detailed explanation can be found elsewhere [17].…”
Section: Corrosion Mechanismsupporting
confidence: 64%
See 2 more Smart Citations
“…Thereby the findings of the EDX mappings and the XRD results can be explained. This mechanism has been identified in previous studies, and a detailed explanation can be found elsewhere [17].…”
Section: Corrosion Mechanismsupporting
confidence: 64%
“…The test gas leaving the test chamber was neutralized in 10% KOH and 10% NaOH solution. A detailed experimental procedure and a scheme of the testing equipment can be found elsewhere [17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After corrosion tests with N10276 under the same conditions as in the prior experiments, the material N10276 showed a different behavior. The results of N10276 are compared with the findings of the materials S31400 and N06600, which were published in previous studies [15,16]. A detailed comparison can be found in the Discussions section in Section 4.3.…”
Section: Introductionmentioning
confidence: 85%
“…These should be specified in future works to find an appropriate reactor material. Thus, the corrosion resistance of several austenitic steels was investigated under conditions simulating the pyrolysis process of our industrial partner and some corrosion mechanisms to explain the formation of the complex corrosion layers for these materials were developed [2,3,15,16].…”
Section: Introductionmentioning
confidence: 99%